Cloning and in silico analysis revealed a genetic variation in osmotin-encoding genes in an Indonesian local cacao cultivar - Imam Bagus Nugroho; Fahrurrozi Fahrurrozi (Universitas Gadjah Mada, 2020)
Theobroma cacao L. is an important Indonesian estate crop, which suffers from biotic and abiotic stresses. TcOSM, which encodes osmotin as a response to pathogens and environmental stresses, is, therefore, a focus of interest in this research, aiming to characterize TcOSM in an Indonesian local cacao cultivar. Bioinformatics queries for putative TcOSM were performed against the reference genome of a Criollo-type cacao cultivar. Based on nucleotide sequence determination, our results revealed two genes, TcOSM1 and TcOSM2, which have the highest similarity (≥ 90%) to the cacao reference genes. Heterozygosity was detected in the TcOSM1-encoding gene, which contained two overlapping peaks in Sanger-sequencing chromatograms. One of the alleles resulted from a single nucleotide change (G to A), leading to a same-sense mutation that did not substitute corresponding alanine residue. Homology modeling using Phyre2 and structural alignment (superimposition) was conducted to examine the influence of genetic variations in TcOSM sequences upon the global protein structures. The result showed no significant changes (RMSD ≤ 0.206 Å, TM-score > 0.5) in tertiary protein structures. Altogether, this research succeeded in characterizing TcOSM while providing a fundamental study for future cacao biotechnology endeavors.